Apatite for destruction: investigating bone degradation due to high acidity at Star Carr. (July 2015) - High, K.; Milner, N.; Panter, I.; Penkman, K.E.H.
Abstract: In order to more fully understand the effects of high acidity on bone at the Mesolithic site of Star Carr, a suite of analytical techniques has been used to assess the effects on the inorganic and organic fractions of treating a range of bone types in different strength sulfuric acid solutions. These include mass loss analysis, scanning electron microscopy, chiral amino acid analysis, and powder X-ray diffraction. Loss of bone mineral is shown to be severely accelerated at low pH and this ultimately leads to increased breakdown of the bone collagen. Archaeological samples are significantly more at risk than modern samples. Reaching an understanding of the effects of increased acidity on organic artefacts through studies such as this has important applications in determining the future management not only of Star Carr, but other sites with similar chemical environments. Highlights: A lab-based approach is used to investigate bone degradation in acidic conditions. A multi-analytical approach is used to quantify deterioration. Rapid loss of bone mineral is seen at low pH. Loss of bone mineral ultimately leads to degradation of the bone collagen. Archaeological bone at Star Carr is at risk of being lost due to site acidification.